Contribution to the knowledge of the Neotropical species of Smeryngolaphria Hermann, 1912 (Diptera: Asilidae: Laphriinae) - Camargo, Alexssandro; Vieira, Rodrigo; Lima, Sheila; Chagas, Cínthia (Zootaxa, 2017)
The male of Smeryngolaphria gurupi Artigas, Papavero & Pimentel, 1988 and the female of Smeryngolaphria taperignae Artigas, Papavero & Pimentel, 1988 are described for the first time. The habitus, thorax, abdomen, male and female terminalia with external and internal structures are illustrated and described. The external and internal structures of the male and female of Smeryngolaphria gorayebi Artigas, Papavero & Pimentel, 1988, Smeryngolaphria maculipennis (Macquart, 1846) and Smeryngolaphria numitor (Osten Sacken, 1887) are described and illustrated, Smeryngolaphria numitor for the first time. A map with the new records is provided.